Improving intranasal delivery of neurological nanomedicine to the olfactory region using magnetophoretic guidance of microsphere carriers - Xi J (Dove Medical Press, 2015)
Jinxiang Xi,1 Ze Zhang,1 Xiuhua A Si21School of Engineering and Technology, Central Michigan University, Mount Pleasant, MI, 2Department of Mechanical Engineering, California Baptist University, Riverside, CA, USABackground: Although direct nose-to-brain drug delivery has multiple advantages, its application is limited by the extremely low delivery efficiency (<1%) to the olfactory region where drugs can enter the brain. It is crucial to developing new methods that can deliver drug particles more effectively to the olfactory region.Materials and methods: We introduced a delivery method that used magnetophoresis to improve olfactory delivery efficiency. The performance of the proposed method was assessed numerically in an image-based human nose model. Influences of the magnet layout, magnet strength, drug-release position, and particle diameter on the olfactory dosage were examined.Results and discussion: Results showed that particle diameter was a critical factor in controlling the motion of nasally inhaled ferromagnetic drug particles. The optimal particle size was found to be approximately 15 µm for effective magnetophoretic guidance while avoiding loss of particles to the walls in the anterior nose. Olfactory delivery efficiency was shown to be sensitive to the position and strength of magnets and the release position of drug particles. The results of this study showed that clinically significant olfactory doses (up to 45%) were feasible using the optimal combination of magnet layout, selective drug release, and microsphere-carrier diameter. A 64-fold-higher delivery of dosage was predicted in the magnetized nose compared to the control case, which did not have a magnetic field. However, the sensitivity of olfactory dosage to operating conditions and the unstable nature of magnetophoresis make controlled guidance of nasally inhaled aerosols still highly challenging.Keywords: direct nose–brain delivery, olfactory deposition, magnetophoretic guidance, neurological nanomedicine, intranasal drug delivery, microsphere carrier